Analisa Biaya Produksi Dalam Penetapan Harga Jual Tray Menggunakan Metode Full Coasting - Ribangun bamban jakaria; Ricky kurniawan; Mukhammad rifky ramadhan; Indra lesmana (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Tray companies have so far used simple methods in determining product selling prices, not calculating the cost of production in detail, such as machine maintenance costs, machine and building depreciation costs. This research aims to find out how to calculate the cost of production to determine the selling price of products at a tray company. The method used in the research is the full coasting method, which is a method for determining the cost of products taking into account all elements of production costs consisting of raw materials, direct labor costs and factory overhead costs, both fixed and variable. The results of this research show that tray production in November was 950 units with the selling price for tray production for determining the selling price for trays per unit was IDR. 425,000. Determining the selling price of the tray using the full coasting method achieves satisfactory profits for the company.